A positive feedback loop between ZNF205‐AS1 and EGR4 promotes non‐small cell lung cancer growth. Issue 2 (16th December 2018) - He, Susu; Lin, Jian; Xu, Youzu; Lin, Ling; Feng, Jiaxi
Abstract: Accumulating evidences revealed that long noncoding RNAs (lncRNAs) are frequently implicated in non‐small cell lung cancer (NSCLC). Herein, we reported the identification of a novel NSCLC‐associated functional lncRNA ZNF205 antisense RNA 1 (ZNF205‐AS1). ZNF205‐AS1 was increased in NSCLC tissues and cell lines, and associated with poor prognosis of NSCLC patients. Bioinformatics prediction, combined with experimental verification revealed that early growth response 4 (EGR4) directly bound to ZNF205‐AS1 promoter, increased the promoter activity of ZNF205‐AS1, and activated ZNF205‐AS1 transcription. Intriguingly, ZNF205‐AS1 transcript directly interacted with EGR4 mRNA, increased EGR4 mRNA stability, and up‐regulated EGR4 expression via RNA‐RNA interaction. Thus, ZNF205‐AS1 and EGR4 formed a positive feedback loop. Through regulating EGR4, ZNF205‐AS1 activated its own promoter activity. EGR4 was also increased in NSCLC and the expression of ZNF205‐AS1 was significantly positively correlated with EGR4 in NSCLC tissues. Gain‐of‐function and loss‐of‐function assays demonstrated that both ZNF205‐AS1 and EGR4 promoted NSCLC cell growth in vitro and NSCLC tumour growth in vivo. Concurrently depleting ZNF205‐AS1 and EGR4 more significantly repressed NSCLC tumour growth in vivo. Collectively, our study demonstrated that the positive feedback loop between ZNF205‐AS1 and EGR4 promotes NSCLC growth, and implied that targeting this feedback loop may be promising therapeutic strategy for NSCLC.